2021
DOI: 10.1016/j.foodcont.2021.108062
|View full text |Cite
|
Sign up to set email alerts
|

Washing hands and risk of cross-contamination during chicken preparation among domestic practitioners in five European countries

Abstract: Washing hands and risk of cross-contamination during chicken preparation among domestic practitioners in five European countries, Food Control,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 35 publications
0
8
0
3
Order By: Relevance
“…Hand washing habit is the important way to prevent cross contamination of pathogens during preparing food. Many people think washing hands with water only and with soap is considered the same (12) . Hand washing habit of community are not in the five important times.…”
Section: Discussionmentioning
confidence: 99%
“…Hand washing habit is the important way to prevent cross contamination of pathogens during preparing food. Many people think washing hands with water only and with soap is considered the same (12) . Hand washing habit of community are not in the five important times.…”
Section: Discussionmentioning
confidence: 99%
“…Hand washing is an important way to prevent cross-contamination with pathogens during food preparation. Many people think that washing hands with water only and washing hands with soap are considered the same thing (5).…”
Section: Habit Of Washing Hands With Soap At Five Important Timesmentioning
confidence: 99%
“…Five hand-cleaning procedures (HCPs) were tested (see Table 1). For HCP3, time for rinsing was set at 5 s because the observational studies performed in SafeConsume [33,34] showed that this is often the case in real-life situations. HCP4 and HCP5 were tested as alternatives for situations when water is not available.…”
Section: Hand-cleaning Proceduresmentioning
confidence: 99%